2003
DOI: 10.1001/archotol.129.9.940
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Electroneurographic Facial Nerve Monitoring in Patients With Parotid Tumors

Abstract: Electroneurography is a sensitive tool for monitoring clinically silent facial nerve function deficits in the context of preoperative tumor-induced damage and postsurgical early and late follow-up of nerve function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The same series of concentrations of muscle relaxant produced a proportionally similar occupation of the residual AChRs in the injured nerve‐innervated muscles to those in the normal nerve‐innervated muscles and created proportionally the same inhibition of muscular tension amplitude. Therefore, the less‐detected muscular contractile responses in the impaired facial nerve‐innervated muscles may merely be a result of the relatively lower density of AChRs at end plates as well as the corresponding smaller basal values of MTA compared to the normal facial nerve‐innervated muscles, and except for the affinity of AChRs to muscle relaxants, this may be the theoretical basis for the clinical phenomenon that the sensitivity of EEMG responses is reduced in patients with impaired facial nerve function 11, 27. In addition, although the affinity of AChRs to muscle relaxants in the orbicularis oris are not affected by acute facial nerve injury, the EEMG response in patients with latent facial nerve injury may still be hardly detected, due to the faster saturation of the relatively lower density of AChRs (i.e., the percentage of inhibition of EEMG may be not influenced whereas the absolute values of EEMG can be reduced).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same series of concentrations of muscle relaxant produced a proportionally similar occupation of the residual AChRs in the injured nerve‐innervated muscles to those in the normal nerve‐innervated muscles and created proportionally the same inhibition of muscular tension amplitude. Therefore, the less‐detected muscular contractile responses in the impaired facial nerve‐innervated muscles may merely be a result of the relatively lower density of AChRs at end plates as well as the corresponding smaller basal values of MTA compared to the normal facial nerve‐innervated muscles, and except for the affinity of AChRs to muscle relaxants, this may be the theoretical basis for the clinical phenomenon that the sensitivity of EEMG responses is reduced in patients with impaired facial nerve function 11, 27. In addition, although the affinity of AChRs to muscle relaxants in the orbicularis oris are not affected by acute facial nerve injury, the EEMG response in patients with latent facial nerve injury may still be hardly detected, due to the faster saturation of the relatively lower density of AChRs (i.e., the percentage of inhibition of EEMG may be not influenced whereas the absolute values of EEMG can be reduced).…”
Section: Discussionmentioning
confidence: 99%
“…EEMG has become increasingly important in identifying emerging irritation or developing injury to the nerve, for example tumor‐related facial nerve injury such as acoustic neuroma, so as to facilitate intervention to reverse the neurophysiologic manifestations 9, 10. The amplitude of EEMG responses was reduced in the patients with impaired facial nerve function before surgery in contrast to those with normal facial nerve function 11. Thus, EEMG monitoring of patients with presurgical or clinically silent facial nerve injuries should be performed with extra caution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it could not be ascertained whether they had definite facial nerve damage [10,11,12]. However, in those patients, the mean difference of FNAEP latency was 0.894 ms (reference value+2 SD) and above; thus it was judged to be abnormal, so it was possible to diagnose facial nerve damage.…”
Section: Resultsmentioning
confidence: 99%
“…EMG detects nerve damage, identifying whether spontaneous abnormal activities occur during the resting state in facial muscles, such as the frontalis, obicularis oculi, and orbicularis oris muscles, and whether motor unit action potential changes occur [2,3,4,5,6,7,8,9,10]. In the case of ENoG, nerve damage is confirmed when waveform amplitude is smaller than half of that on the unaffected side [10,11,12]. However, both tests may be less accurate when they are performed within a week after the onset of Bell's palsy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the majority of patients will likely have different degrees of facial nerve injury before surgery, and the EEMG response may have already decreased due to inflammation, trauma or tumor compression 5 . Our previous study also showed that the EEMG response is affected more by facial nerve injury of greater severity 6 .…”
Section: Introductionmentioning
confidence: 99%